Vieses orçamentários em entes subnacionais: uma análise sob a ótica da estimação das receitas estaduais - Fajardo, Bernardo de Abreu Guelber (2016)
This study presents the thesis that the Brazilian states have an incentive to manipulate its budget revenues’ forecast aiming to expand its discretion in the management of public accounts as a way to escape the limitations imposed by the national federal structure (in political, fiscal and administrative aspects). We start from the assumption that because of the institutional similarity between the state level and the federal level, the strategic behavior of budget revenues’ forecast would be similar to the behavior performed by the incumbent of the central entity. This presupposes that state executives tend to overestimate their budget revenues to accommodate the wishes of state legislators - as described by Pereira and Mueller (2014). The observation of empirical data, however, shows that at specific times, state executives underestimate their budget revenues’ forecasts. The investigation into the apparent contradiction in the behavior of the agents is what motivates the realization of this thesis. Regarding the complexity surrounding the forecast process of budget revenues (Beaver, 1991) in order to give greater rigor to these results, we propose an algebraic exercise to identify the amount of prediction error that can be attributed to the state executives’ discretionary budget manipulation, separating other components as errors arising from random aspects. This exercise is performed for the Total Reveue and for the main component of the states’ Budget Revenue (Tax Revenue), aiming to capture differences in behavior between such items, as noted by Aquino and Azevedo (2015). Finally, econometric panel data models are used to test hypotheses concerning the Brazilian federalism (in its fiscal, political and administrative aspects) to justify the share of discretionary error in each of the analyzed items. The results support the thesis presented, identifying that the Brazilian states use the forecast of discretionary budget revenues according to their momentary needs, so that when it identifies the need to enlarge the support of the Legislative Assembly, it overestimates budgeted revenues to facilitate the accommodation of requests from state parliament. Conversely, in times in which identifies fiscal pressure, the state underestimates up their budget revenues to request more funds transfer from the federal government